A situation analysis of psychiatrists in South Africa's rural primary healthcare settings - Johannes H. De Kock; Basil J. Pillay (AOSIS, 2017)
Background: South Africa (SA) has been facing serious challenges in providing human resources for the delivery of essential mental health (MH) services. The majority of its prescribing MH specialists, psychiatrists, practise in private, urban and peri-urban areas. The findings of a situation analysis audit of psychiatrist human resources in the public rural primary healthcare (PRPHC) sector are presented in this paper. Method: This audit was based on both primary and secondary data. The primary data were obtained from key informant interviews with the clinical heads of 160 PRPHC facilities, while the secondary data comprised a literature review. Results: The results indicate that psychiatrists are severely underrepresented, employed at a rate of 0.03 per 100 000 population in SA's PRPHC settings. Conclusions: Because of a lack of MH nurses and medical officers dedicated to MH in PRPHC facilities, recommendations are made that the current task shifting strategy be revisited to include more cadres of MH professionals with specialised psychopharmacological training, as non-medical prescribers at PRPHC level. It is advised that visiting psychiatrists and family physicians be involved in the construction of training and supervision programmes for non-medical prescribers at the primary healthcare level.